Faultlines of Conflict in Central Asia and the South Caucasus Implications for the U.S. Army - Oliker, Olga (RAND Corporation, 2003)
In the region of Central Asia and South Caucasus, what is the potential for armed conflict, and how might such outbreaks escalate to a level that could involve U.S. forces? The authors evaluate the key political, economic, and societal faultlines underlying the likelihood of conflict in the region, assessing their implications for regional stability and for U.S. interests and potential involvement over the next 10 to 15 years.